2014
DOI: 10.1002/mrd.22444
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of activity and concentration of paraoxonase 1 (PON‐1) in seminal plasma and identification of PON‐2 in the sperm of boar ejaculates

Abstract: Abbreviations: BTS, Beltsville thawing solution; HDL-C, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; LPO, peroxidation of membrane lipids; OS, oxidative stress; PBS, EDTA-free phosphate-buffered saline; PON, paraoxonase; ROS, reactive oxygen species; RT, room temperature; SP, seminal plasma. 3 ABSTRACTThis study revealed and characterised the presence of the antioxidant enzymes paraoxonase (PON) type 1 (PON-1, extracellular) and type 2 (PON-2, intracellular) in boar semen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Therefore, the spermatozoa benefit from the presence of antioxidant components in the seminal plasma (SP) in which they are bathed (Juyena & Stelletta, ). The boar SP contains antioxidant enzymes (Strzezek, ), including paraoxonase 1 (PON‐1) (Barranco et al ., ); an extracellular high‐density lipoprotein (HDL)‐associated enzyme that possess antioxidant and anti‐inflammatory properties, which prevents low‐density lipoprotein and HDL oxidation and, consequently, protects cells against OS (Camps et al ., ). In humans, lowered SP‐PON‐1 levels have been related to increased OS and infertility (Verit et al ., ; Lazaros et al ., ), and SP‐PON‐1 activity has been positively correlated with sperm parameters, such as concentration, motility, and morphology (Verit et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the spermatozoa benefit from the presence of antioxidant components in the seminal plasma (SP) in which they are bathed (Juyena & Stelletta, ). The boar SP contains antioxidant enzymes (Strzezek, ), including paraoxonase 1 (PON‐1) (Barranco et al ., ); an extracellular high‐density lipoprotein (HDL)‐associated enzyme that possess antioxidant and anti‐inflammatory properties, which prevents low‐density lipoprotein and HDL oxidation and, consequently, protects cells against OS (Camps et al ., ). In humans, lowered SP‐PON‐1 levels have been related to increased OS and infertility (Verit et al ., ; Lazaros et al ., ), and SP‐PON‐1 activity has been positively correlated with sperm parameters, such as concentration, motility, and morphology (Verit et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Sperm cell structure and function depend on the lipid composition in sperm cells and SP (Barranco et al, 2015;Wood et al, 2016) which in turn affect its fertilisation capacity. Cholesterol is a key factor in semen quality and function where analysis of semen samples from stallions with unexplained subfertility revealed a low concentration of SP cholesterol (Brinsko et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Barranco et al [97] revealed and characterized the presence of the antioxidant enzymes PON-1 and PON-2 in boar semen. PON-1 binds to membrane cholesterol, preventing its oxidation and thereby positively influencing both motility and the sperm membrane integrity [46].…”
Section: Paraoxonase Typementioning
confidence: 99%